Sur les traces des savants d’Agadez au tournant du XXe siècle. Traduction d’un manuscrit de Bukhārī Tānūdé (écrit vers 1967-1969) - Salao Alassane (Afriques)
This article offers us a translation of a manuscript, Miṣbāḥ al- Ẓalām fī wafayāt Aʿyān al-qarn al- ṯāliṯ ʿašar ilā al-rābiʿ ʿašar, written between 1967 and 1969 by Tānūdé b. al-Bukhārī b. Ilāǧāl al-Tinbuktī al-Agadazī. Preserved at the Department of Arabic and Ajami Manuscripts (MARA) of the Institut de Recherches en Sciences Humaines of the Abdou Moumouni University of Niamey, this text sheds light, in the form of short biographical notes, on the training and career of several Muslim scholars from the city of Agadez who lived mainly between the early 19th century and the 1920s (c. 1214-1344 AH).